Cows visually discriminate and cross-modally recognise familiar and unfamiliar human faces in videos - Océane Amichaud; Julie Lemarchand; Fabien Cornilleau; Plotine Jardat; Vitor H. B. Ferreira; Ludovic Calandreau; Léa Lansade (PLoS ONE, 2026)
Social recognition has been studied and demonstrated in many species. In domesticated species, the long evolutionary history shared with humans has led to investigations into their cognitive abilities towards humans, particularly regarding discrimination and recognition of humans. The present study investigated whether cows are capable of visual discrimination and cross-modal recognition of familiar and unfamiliar humans. Thirty-two cows were exposed to two tests: a visual preference test, during which two silent videos were shown simultaneously – each displaying either a familiar or an unfamiliar human face – and a cross-modal test, during which the videos were accompanied by either a congruent or incongruent voice. During the visual preference test, cows looked significantly longer at the video showing the unfamiliar person (p = 0.028). In the cross-modal test, they looked significantly longer at the video that was congruent with the voice being played (p = 0.014). These two results show that cows are able to discriminate between familiar and unfamiliar individuals and form cross-modal representations of these people. Based on these results, future research should explore whether cows can adjust their behaviour depending on the person they are interacting with – a capacity that may reflect their agency in human-animal relationships.